Assessing the effect of plant surface on the predatory ability of Orius vicinus : a potential biological control agent of the tomato-potato psyllid (Bactericera cockerelli) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Zoology at Massey University, Palmerston North, New Zealand - Gamarra Landa, Abel (Massey University, 2019)
The tomato-potato psyllid (TPP), Bactericera cockerelli (Sulc), is a pest to solanaceous crops (e.g. potato, tomato, peppers, and eggplant) and is associated with economically important plant diseases. Subsequently, chemical control is the preferred management option. However, chemical reliance is associated with a host of issues. The development of biological control methods is vital to implementing Integrated Pest Management (IPM) programs as an alternative to broad-spectrum insecticide usage. The predatory bug Orius vicinus (Ribaut) is a potential biological control agent that is capable of consuming all nymphal life stages of TPP. In order to be a commercially viable management option, potential biological control agents of TPP have to cope with the different morphological plant features of the pest’s wide range of host plants. Tomato and capsicum plant surfaces were selected as the experimental surfaces for my thesis because they differ significantly in their substrate morphology. Tomato plant surfaces can be a hostile environment for potential biological control agents due to the negative effect tomato trichomes have on their foraging performance. Alternatively, because capsicum plant surfaces are virtually void of trichomes they appear to be more suitable for effective biological control agent deployment. I exposed the predatory bug to a variety of TPP nymph densities (10, 20, 30 and 40 individuals) in order to determine the functional response of O. vicinus. Furthermore, the predatory bug was exposed to all five TPP nymphal stages simultaneously. The predatory performance of O. vicinus was also assessed on experimental arenas varying in complexity (leaflet vs. small plant environments). The functional response was determined to be Type II on both plant surfaces. Nymph consumption at higher prey densities (30 and 40 nymphs) was significantly greater on capsicum than on tomato. Nymph consumption at lower prey densities (10 and 20 nymphs) was only significantly greater on capsicum when the complexity of the experimental arena increased from leaflet to small plant. The influence of O. vicinus in nymph dispersal was also assessed. My results revealed that the presence of O. vicinus increased the dispersal of nymphs to lower leaf surfaces and that nymph dispersal was significantly greater on capsicum than on tomato. TPP nymph size preference by O. vicinus was determined in my study. I established that the predatory bug is capable of killing all nymphal stages. My study strongly indicated that the predatory bug is more likely to target and consume medium (3rd instars) and large nymphs (4th and 5th instars) over small nymphs (1st and 2nd instars). I investigated the behaviour of O. vicinus adults and TPP nymphs during their interactions via video recordings. The predatory bug spent a significantly greater amount of time investigating TPP nymphs on capsicum than on tomato. There was significantly higher number of attacks recorded on capsicum. The greater killing percentage on tomato suggests that the defensive capabilities of TPP nymphs appear to have been negatively affected by the tomato substrate. The results from my study indicate that augmentative releases of O. vicinus, in the presence of smaller TPP nymphs, could be a viable biological control option on capsicum plants. However, the predatory bug will likely struggle if deployed on tomato plants. Future studies should be conducted in settings such as open field or glasshouses using multiple predatory bugs in the presence of susceptible life stages to assess augmentative release efficiency.
Keywords: Anthocoridae; Behavior; Paratrioza cockerelli; Biological control; Plant surfaces; Tomatoes; Peppers; Morphology; tomato-potato psyllid (TPP); Bactericera cockerelli; Orius vicinus; functional response; prey preference; plant surface morphology; capsicum; tomato; 310901 Animal behaviour